Rapid oxygen diffusive lithium–oxygen batteries using a restacking-inhibited, free-standing graphene cathode film. Issue 17 (5th April 2019) - Jung, In-Sun; Kwon, Hyuk Jae; Kim, Mokwon; Kim, Doyoung; Kim, Jung-Hwa; Lee, Hyangsook; Yun, Dongjin; Byun, Sunjung; Yu, Daeun; An, Hyunju; Jang, Jaeduck; Im, Dongmin; et al.
Abstract : The rapid oxygen diffusion of corrugated 2D graphene sheets enhances the capacity and cycle life of lithium air batteries. Abstract : A graphene-based porous electrode for a lithium–oxygen (Li–O2 ) battery is investigated for use in next generation energy storage systems. The porosity of the cathode electrode in Li–O2 batteries is a key factor in increasing their oxygen diffusion rate and electrochemical activity, and enables a longer cycle life. In addition, the adsorption behavior of the electrolyte is an important factor for the charging process and diffusion of oxygen. We report the fabrication of a restacking-inhibited film cathode using corrugated and highly porous reduced graphene flakes that have an outstanding capacity and cycle life. We have demonstrated a robust porous cathode film for the next generation Li–O2 batteries, which provides (1) rich voids and spaces for oxygen-related reactions, (2) easy accessibility to the electrolyte and rapid oxygen diffusion. This study can be applied for the design of new solution-processed graphene and the development of Li–O2 battery cathodes.